Nilai-Nilai Pendidikan Islam Berbasis Multikultural dalam Film Upin dan Ipin - Yusnil Khoiriah Siregar; Rengga Satria; Ageng Priadi (Prodi Pendidikan Keagamaan Islam, 2022)
This study aims to analyze the values of multicultural-based Islamic education in the film Upin and Ipin episodes of fasting experience, gong xi fa cai, and Deepavali. There are five values in multicultural-based Islamic education, namely tolerance, pluralism, humanism, equality, democracy, and justice. The fasting experience episode has two values, then the gong xi fa cai episode has five values while the Deepavalii episode has four values. The data analysis of this research used content analysis with a semiotic approach. The results of the research on the Upin and Ipin films of this fasting experience episode, gong xi fa cai and Deepavali contain all these values that can be used by children as examples in instilling the value of multicultural-based Islamic education as an effort to prevent the division of mankind.